KEFIR DAN PENGARUHNYA TERHADAP ASUPAN DAN LAMA HARI RAWAT PASIEN COVID-19 DI RSUD HAJI PROVINSI JAWA TIMUR (TEMU ILMIAH NASIONAL PERSAGI, 2023)
COVID-19 Patients need to increase their immune system. Probiotic drinks can eliminate viruses that enter the body’s defense system. So the researchers made kefir, a probiotic drinks with the aim of helping patients speed up healing. Objective to determine the effect of giving kefir, probiotic drinks on the intake and length of stay COVID-19 patients with The Hight Energy High Protein (TETP) diet and The Diabetes Mellitus (DM) diet. Methods Quantitative research with a quasi-experimental design in the COVID-19 isolation room for the period February-March 2022 as many as 70 patients. Results there was a significant difference in intake between the control group and the intervention group (p=0,027) in patients on the TETP diet and in patients on the DM diet (p=0,063). There was no difference in length of stay between the control group and the intervention group (p=0,900) in patients on the TETP diet and patients on the DM diet (p=0,063). Conclusion giving fermented kefir milk is effective in increasing the patient’s food intake even though it has no impact on the length of stay of COVID-19 patients. Recommendation need to do research related to the effective duration of giving kefir.